ANALISIS PELAKSANAAN PENYALURAN KREDIT USAHA KECIL MENENGAH DALAM MENGATASI KREDIT MACET (STUDI KASUS PENYALURAN KREDIT BANK PERKREDITAN RAKYAT (BPR) HARTA MANDIRI DI PEKANBARU) - Ari Mujahidin; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
As a small business, the small and medium business unit in desperate need of financial assistance. One lender capital is PT. BPR Harta Mandiri Perkasa Cabang Pekanbaru. From the capital, the expected presence of small and medium businesses can thrive even in business. But in fact small and medium businesses have not been able to properly carry out their business in a profit. This leads to capital provided by BPR to become obstructed pengembaliannnya. Because capital is given a credit in the form of venture capital. With the ability of small and medium enterprises that are less so that the creation of bad loans that can be suffered by the RB. In addition to the loss of RB, also the loss of small and medium business unit itself.PT. BPR Harta Mandiri Perkasa Cabang Pekanbaru activity, in addition to lending to small and medium business unit, also lending to the general public in the form of credit is a credit for residential housekeeping. Activities PT. BPR Harta Mandiri Perkasa Cabang Pekanbaru olso provide savings and current accounts and deposits.The purpose of this study was to determine and analyze the implementation of small and medium enterprise lending banking sector in evaluating bad loans on PT. BPR Harta Mandiri Perkasa Cabang Pekanbaru.The results of the study concluded that the binding of the less than perfect credit guarantees are common in this bank. This is confirmed interviews with head xxxxxxxxxxxxx many cases binding guarantees less than perfect credit. But thankfully it did not lead to bad credit because fieldworkers who conducted a survey has provided confidence in the outstanding loans. acyl respondents indicate that the binding of a less than perfect credit guarantees can lead to bad credit. But in this bank, an increase in collateral rated as good by a majority of respondents. Thus, given the collateral can be used as collateral if the bad loans. Keywords: Small And Medium Businesses Lending, Bad Debt